Cytogenetics of four species of Spirostreptidae (Diplopoda, Spirostreptida) - Preto de Godoy, Juliana Aparecida [UNESP]; Braga Pierozzi, Pedro Henrique [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Considering an estimated number of millipedes of approximately 80,000, cytogenetic studies on these animals are rare, as only a total of 70 species have their karyotypes described. The present study reports on the chromosomal number of four Brazilian diplopods of the family Spirostreptidae: Urostreptus atrobrunneus with 2n = 24, XY; Gymnostreptus olivaceus 2n = 12, XY and Alloporus araraquarensis and A. principes, 2n = 18, XY. The C-banding pattern and NOR staining of U. atrobrunneus, G. olivaceus and A. araraquarensis are described. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Millipede; NOR; C-banding; Chromosomes; Heterochromatin